Map of Policies Supporting Thermal Efficiency in Germany's Residential Building Sector - Hermann Amecke; Karsten Neuhoff (Climate Policy Initiative, 2011)
Executive Summary The German government aims to reduce primary energy demand by 80% until 2050 and heating demand by 20% until 2020. Besides the need for additional efforts to achieve these targets, Germany has already implemented a set of policies and programmes to increase investments in thermal energy efficiency. This paper provides an overview of currently implemented German policies, specifically addressing two questions: A) What roles do different types of policies play in supporting energy efficiency in the residential building sector and how do they interact? B) In Germany, which policies fulfil these roles? How do they perform? The report covers all main federal policies in Germany and reviews the current literature on the impact of the individual policy tools. The following summarizes the paper's key points: A) What roles do different types of policies play in supporting thermal energy efficiency investments and how do they interact? There are three key categories of energy efficiency policies for buildings in Germany: i) financial instruments to improve the economics of thermal energy efficiency measures, ii) information instruments to highlight advantages and options for investing into energy efficiency, and iii) standards mandating performance requirements. Interactions among these policies impact their overall effectiveness. Building policies are complementary because they fulfil different roles and respond to different needs; a single program is often not effective without the support of other mechanisms. For instance, for a loan or financing instrument to work, information instruments are needed to communicate the additional savings they offer. Applications to a programme with the same financial benefits can be increased manifold by alterations to the information provided. Equally, financial support programs increase the interest in and relevance of information instruments to building owners. Besides the needs for a balanced policy mix, some policies can also act as substitutes to each other. Energy demand reductions can, for example, be either triggered by enhancing the profitability of energy efficiency technologies through financial support or by compulsory performance standards, depending on the policy preference of a government. B) In Germany, which policies fulfil these roles? How do they perform? Note: The charts below for each type of policy list key policies in Germany. Detailed descriptions of each policy are found in this paper. I. Financial policies improve the economics of investments by addressing different needs and preferences of building owners. The following chart lists German policies that improve the economics of energy performance investments by either providing access to preferential finance or upfront support, changing heating costs, or aligning incentives. A diversity of financial support mechanisms is suggested to increase the impact of financial support because different actors prefer and/or need different support mechanisms.
Keywords: H31; Q48; R38; 330; Policy mix; energy efficiency; Policy mix; Energy efficient building; Energy saving